2012
DOI: 10.1111/j.1420-9101.2012.02561.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of size of the uropygial gland: mutualistic feather mites and uropygial secretion reduce bacterial loads of eggshells and hatching failures of European birds

Abstract: Potentially, pathogenic bacteria are one of the main infective agents against which a battery of chemical and physical barriers has evolved in animals. Among these are the secretions by the exocrine uropygial gland in birds. The antimicrobial properties of uropygial secretions may prevent colonization and growth of microorganisms on feathers, skin and eggshells. However, uropygial gland secretions also favour the proliferation of feather mites that feed on secretions and microorganisms living on feathers that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 62 publications
2
66
0
Order By: Relevance
“…This could explain the fact that both lipids and glycoproteins are secreted along the adenomer. Some of these glycoproteins may have functions related to protection from pathogenic agents (Soler et al 2012). In marine mammals, it has been demonstrated that some cutaneous glands produce glycoproteins with microbicidal action (Meyer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain the fact that both lipids and glycoproteins are secreted along the adenomer. Some of these glycoproteins may have functions related to protection from pathogenic agents (Soler et al 2012). In marine mammals, it has been demonstrated that some cutaneous glands produce glycoproteins with microbicidal action (Meyer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Its secretion confers water-repellent properties to the feather coat and also maintains the suppleness of the feathers. Other physiological roles of the secretion of the uropygial gland may be associated with pheromone production, control of plumage hygiene, thermal insulation and defence against bacteria and predators Bhattacharyya 1996, 1999;Montalti et al 2006;Salibián and Montalti 2009;Møller et al 2010;Soler et al 2012;Vincze et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus there should be strong selection on parasites to develop antimicrobial defences against the bacteria of hosts, while the reverse would not be the case. A thick eggshell is a mechanical defence against microorganisms (Board et al, 1994), and embryo mortality due to microorganisms is common in chicken (Baggott and GraemeCook, 2002) and in many species of wild birds (Soler et al, 2012b). Extensive studies of eggshell strength in chickens have provided evidence for an optimal egg shape with an optimal size and density of eggshell pores (Solomon et al, 1994).…”
Section: Anti-bacterial Protection Hypothesismentioning
confidence: 99%
“…There are many accepted functions of gland secretions like conferring waterrepellent properties on the feather coat and maintaining the suppleness of it. Furthermore, it's proposed to be associated to pheromone production, control of plumage hygiene, thermal insulation and defense against predators (Jacob, 1992;Montalti et al, 2006;1998;Soler et al, 2012;Vincze et al, 2013). Uropygial gland is completely absent in Struthionidae, Rheidae, Casuaridae, Dromaidae and in a few species of Columbidae and Psittacidae (Johnston, 1988).…”
Section: Introductionmentioning
confidence: 99%